Asesmen Diagnostik Gaya Belajar Siswa Kelas VII di SMPN 4 Padang Panjang - Ermiyanto Ermiyanto; Iman Asroa B.S; Asnelly Ilyas (MANAZHIM, 2023)
The learning style diagnostic assessment is one of the main assessments that must be carried out in the independent curriculum. This study aims to raise the learning styles of class VII students at SMPN 4 Padang Panjang. The research question raised is what is the learning style of class VII students at SMPN 4 Padang Panjang? The research was conducted at SMPN 4 Padang Panjang by distributing a learning style questionnaire to students. The research population consisted of all students in class VII at SMPN 4 Padang Panjang and the sample was taken from students in class VII.I. The research was conducted on December 12, 2022 at SMPN 4 Padang Panjang. The results of the study describe the learning styles of class VII students at SMPN 4 Padang Panjang varying with a ratio of 33.9% to visual learning styles, 33.2% to auditory learning styles and 32.9% to kinesthetic learning styles. These learning style variations are spread out in relatively equal comparisons.